The Effect Of Surface Modification On Activated Carbon Using Citric Acid And Nitric Acid For Copper Removal - Hasan, Norwanis (2007)
Studies on the effects of surface modification on activated carbon (AC) was carried out by oxidizing agents for removal of copper (Cu) in low concentration. A locally produced coconut shell-based activated carbon (AC) was obtained from Versatec Industries in lpoh, Perak was used in this study. The AC used were of 8x30 mesh (ACVA) and 20x50 mesh (ACVE) sizes. Both AC were modified with 1 M citric acid (CA) and concentrated nitric acid (69%HNO3) followed by further treatment with sodium hydroxide (NaOH) . These modified and unmodified AC were used in a series of kinetic and isotherm batch studies.